Registration of Interfaith Marriages from Maqashid Al-Syari'ah Perspective - Alvin M. Iqbal; Imron Sodiq (Journal of Islamic Studies and Civilization, 2023)
Interfaith marriage today has become a social reality that cannot be avoided. Around the end of June 2022, there was a phenomenon of the acceptance of interfaith marriages by the Surabaya District Court. It suddenly made the clergy furious. Institutions like the MUI even asked the related court to cancel the decision. Apart from that, this paper wants to look at the problem of registering interfaith marriages from the perspective of Maqashid Al-Shari'ah. After conducting a study through the lens of Maqashid Al-shari'ah, the registration of interfaith marriages in the end, according to the author's conclusion, is maslahat juziyat hajiyat, which has been upgraded to maslahat juziyat daruriyat. Therefore, registering interfaith marriages is an important matter that the State must regulate and legalize.